2021
DOI: 10.5812/ijcm.111319
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of Iris germanica L. Rhizomes Extract on Human Melanoma Cell Line

Abstract: Background: Melanoma is the leading cause of 80% of skin cancer worldwide due to its high proliferation rate, metastatic nature, and limited effective therapies. Given the rapid increase in its incidence compared to other skin cancers, new therapeutic agents are needed to control the disease. Scientists are interested in medicinal plants due to their anticancer properties. The rhizomes of the Iris germanica L., known as “Irsa”, is one of the herbs used in traditional Persian medicine for the treatment of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Recently, an article was published about the cytotoxic effects of Iris germanica L. on melanoma cells, which showed that this plant could increase the death of cancer cells (Iranzadasl et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an article was published about the cytotoxic effects of Iris germanica L. on melanoma cells, which showed that this plant could increase the death of cancer cells (Iranzadasl et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was measured using the PRISM program. Then, the cytotoxic effects of Polypodium vulgare extract on melanoma cells compared to normal human fibroblasts had read by ELISA (Iranzadasl et al, 2021).…”
Section: Mtt Assaymentioning
confidence: 99%
“…In conclusion, natural products especially herbal products are important in cancer therapy because of their reachability, safety, innocuity, inexpensiveness, proficiency, and being hostile to malignant capacity. Phytochemicals have revealed a significant therapeutic role in various malignancies, however, natural polyphenol compounds (specially flavonoids) represent a broad and assorted group in different types of cancers and even other diseases (Hashem-Dabaghian et al, 2022;Hazafa et al, 2020;Jamshidi et al, 2020;Kenari et al, 2021). Natural polyphenols have their own anticancer efficacy through various pathways.…”
Section: Lipid Peroxidation Assaymentioning
confidence: 99%
“…In a study by Abu Hazafa and his colleagues, the use of herbal compounds and especially polyphenols could be helpful in the treatment of various cancers through molecular mechanisms (Hazafa et al, 2020). Previous studies reported the effectiveness of natural products in the treatment of malignant melanoma (Gladfelter et al, 2017;Iranzadasl et al, 2021). Quercus Brantii Lindl.…”
Section: Introductionmentioning
confidence: 99%